Proceedings of the 4th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle 2007
DOI: 10.17077/drivingassessment.1259
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Motor Vehicle Crashes: A Systematic Evidence-Based Review and Meta-Analysis

Abstract: Summary:The primary objective of this systematic review was to address the question, "Are drivers with diabetes mellitus at greater risk for a motor vehicle crash than comparable drivers without the disease?" and secondarily, to address the question, "Are insulin-treated diabetics at higher risk for crash?" Our searches identified 16 articles that addressed these questions. An assessment of study quality of the included studies found them to be in the low-to-moderate range. While attempts were made to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…Although sleep-deprived healthy drivers probably cause most of these crashes [2], many are the result of drivers with sleep disorders, such as obstructive sleep apnea (OSA). OSA drivers may be especially unsafe, as recent meta-analyses have shown a mean crash risk ratio of 2.72, indicating that these individuals have a 172% greater chance of a crash relative to the general population [3, 4]. Motor vehicle crashes from improperly treated OSA lead to enormous suffering and annual costs that may exceed $11 billion [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although sleep-deprived healthy drivers probably cause most of these crashes [2], many are the result of drivers with sleep disorders, such as obstructive sleep apnea (OSA). OSA drivers may be especially unsafe, as recent meta-analyses have shown a mean crash risk ratio of 2.72, indicating that these individuals have a 172% greater chance of a crash relative to the general population [3, 4]. Motor vehicle crashes from improperly treated OSA lead to enormous suffering and annual costs that may exceed $11 billion [3].…”
Section: Introductionmentioning
confidence: 99%
“…Drivers with obstructive sleep apnea (OSA) have a crash risk that is more than twice that of the general population (Tregear et al, 2008). Sleepiness-related cognitive impairments, which reduce driver performance and increase the likelihood of driver errors that result in crashes, may play a key role.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, when the type of diabetes is controlled for, insulin therapy per se has not been found to be associated with increased driving risk (3,16,17). While impaired awareness of hypoglycemia has been found to relate to increased incidence of motor vehicle crashes in some studies (12), it has not been found to be a relevant variable in other studies (4,7,23).…”
Section: Understanding the Risk Of Diabetes And Drivingmentioning
confidence: 99%